TEACHING ENGLISH AS A SECOND LANGUAGE BEFORE AND AFTER PUBERTY - Khabijonova Maftunakhon Shokirjonovna (The Conference Hub, 2025)
The age at which individuals learn a second language has been a subject of considerable interest in the field of Second Language Acquisition (SLA). This article examines the effects of age, specifically before and after puberty, on the acquisition of English as a second language. By exploring cognitive, social, and psychological factors that influence language learning at different developmental stages, this study aims to elucidate the implications for teaching English as a second language to learners before and after puberty. Insights from critical period theories, empirical research, and teaching methodologies will be discussed to provide a comprehensive understanding of language learning outcomes in these distinct age groups.
Keywords: Teaching English as a Second Language, age effects, puberty, Second Language Acquisition, language learning outcomes